AKURASI HISAB AWAL BULAN QAMARIYAH DALAM KITAB KHULASHAH AL-WAFIYAH & EPHEMERIS - Watni Marpaung, Fika Andriana, Asmuni, (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-undangan, Ekonomi Islam, 2017)
This research aims to analyze deeply about: 1) The method of determining the beginning of qamariyah month according to  the  book  of  Khulashah  al-Wafiyah,  2)  The  method  of determining  the  beginning  of  qamariyah  month  according Ephemeris,  3)  Hisab  accuracy  level  in  determining  the beginning  of  qamariyah  month  according  to  the  book  of Khulashah  al-Wafiyah  and  Ephemeris.  This  research  is  a library  research  in  the  form  of  qualitative  descriptive- analytical  research.  The  primary  data  source  are  the Khulashah al-Wafiyah and The Ephemeris, while secondary data obtained through the study of various related literature. Then  the  data  is  analyzed  by  content  analysis. The  results showed  that  the  method  of  determining  the  beginning  of qamariyah month according to Khulashah al-Wafiyah book in advance through calculation taqribi with reference to the data in the table that is already provided at the end of the book.  Based  on  the  calculation  of  the  intrinsic  taqribi followed  by  calculation  five  correction  to  the  moon?s  data. When applied to the hisab of the beginning of Shawwal 1437 H  /  2016  M,  the  results  show  that  hilal?s  high negative  or position of the moon is still below the horizon. This according with the facts that occurred on the ground when it was that the  height  of  the  new  moon  is  still  negative  so  that  the Ramadhan  in  istikmal  right  to  30  days.  Similarly,  the results  of  the  hisab  of  Syawwal  1437  H  according  to Ephemeris  which  also  showed  negative  height  of  the  new moon.  Thus,  the  accuracy  in  determining  the  beginning  of the month of qamariyah according to the book of al-Wafiyah Khulashah  classified  as  already  a  high  degree  of  accuracy that can even match the real of contemporary hisab.